Traders in motion : identities and contestations in the Vietnamese marketplace - Endres, Kirsten W.; Leshkowich, Ann Marie; Turner, Sarah, 1970- (Southeast Asia Program Publications, an imprint of Cornell University Press, 2018)
With essays covering diverse topics, from seafood trade across the Vietnam-China border, to street traders in Hanoi, to gold shops in Ho Chi Minh City, Traders in Motion spans the fields of economic and political anthropology, geography, and sociology to illuminate how Vietnam's rapidly expanding market economy is formed and transformed by everyday interactions among traders, suppliers, customers, family members, neighbors, and officials. The contributions shed light on the micropolitics of local-level economic agency in the paradoxical context of Vietnam's socialist orientation and its contemporary neoliberal economic and social transformation. The essays examine how Vietnamese traders and officials engage in on-the-ground contestations to define space, promote or limit mobility, and establish borders, both physical and conceptual. The contributors show how trading experiences shape individuals' notions of self and personhood, not just as economic actors, but also in terms of gender, region, and ethnicity. Traders in Motion affords rich comparative insight into how markets form and transform and what those changes mean. Contributors:Lisa Barthelmes, Christine Bonnin, Gracia Clark, Annuska Derks, Kirsten W. Endres, Chris Gregory, Caroline Grillot, Erik Harms, Esther Horat, Gertrud Hüwelmeier, Ann Marie Leshkowich, Hy Van Luong, Minh T.N. Nguyen, Nguyen Thi Thanh Binh, Linda J. Seligmann, Allison Truitt, Sarah Turner.